The Information Security Risks of the BYOD - Fehér-Polgár, Pál; Michelberger, Pál (International Journal of Engineering and Management Sciences, 2018)
Today we cannot imagine our everyday lives without using our smart devices. While commuting we often get into people - even literally - who are doing their work on their portable devices 24 hours a day. This habit is widespread; there are many solutions that can be used by the corporation to have their employees work on their private devices, besides using it in their personal life. They can use these devices at their home, while commuting, or even while being at their own cubicle at the firm. In this article, we are concentrating on the IT risks of the firm with this work practice from a theoretical point of view. After this step, we will continue our research with investigating the problem of measuring and mitigating of these risks.